SOP: Corpus Cavernosum Assessment (Cavernosography/Cavernosometry). (12th September 2012) - Glina, Sidney; Ghanem, Hussein
ABSTRACT Introduction. There is no universal gold standard diagnostic test to differentiate psychogenic from organic erectile dysfunction (ED). Cavernosography/cavernosometry has been used to evaluate veno‐occlusive dysfunction (VOD) in men with a proposed organic ED. Aim. To develop evidence‐based guidelines for the performance and interpretation of cavernosography/cavernosometry. Methods. Review the methodology behind cavernosography/cavernosometry and evaluate the evidence that supports its use and interpretation of results. Main Outcome Measure. Expert opinion based on review of the literature, extensive internal committee discussion, public presentation, and debate. Results. The detailed technique of cavernosography/cavernosometry is described. An evidence‐based perspective to the use and interpretation of cavernosometry is presented. Conclusion. The positive predictive value of cavernosometry still needs further assessment. It is unknown how many potent men would test positive for VOD (false positive). Glina S and Ghanem H. SOP: Corpus cavernosum assessment (cavernosography/cavernosometry). J Sex Med **;**:**–**.